A constituição do Ehos retórico da mulher contemporânea na revista Nova: nova mesmo? - Lois, Márcia Acebedo (2011)
The present work aims to verify how is the constitution of the female ethos by NOVA magazine presented during a period of four years, by a comparative analysis of two samples organized in chronological order. The first was chosen from the magazine birthday edition, in September 2007 and the second was taken from the January edition, 2011. The samples were chosen by corresponding to proposals of behavior rules to the readers, which provide a detailed analysis, so that the ethos of contemporary woman could be obtained. In order to guarantee a satisfactory analysis, historical and theoretical considerations about the Classical Rhetoric and the New Rhetoric, based in C. Perelman & L. Olbrechts-Tyteca, M. Meyer, O. Reboul, J. Dubois, L. L. Mosca, T. L. Halliday and S. L Silva studies applied to advertising language are exposed. For the analysis, L. A. Ferreira studies corresponding to rhetorical analysis principles, with pedagogically systematized categories, are used. P. Abramo considerations about the press manipulation with commercial objectives are also used